The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1464420719876965
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical joining of sheets to tubes by squeeze-grooving

Abstract: The purpose of this paper is to present a mechanical joining process to produce sheet-tube connections in a single stroke, at room temperature. The proposed solution is an enhancement of a previous joining by squeeze-grooving process that makes use of two independent mandrels and a customized spacer to control the inner joint radius and to improve its overall aesthetics. The presentation is illustrated with selected examples retrieved from experimentation and finite element modeling. Results show that the new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…To control this, joining by the squeezegrooving process is introduced which makes use of two independent mandrels. Results indicate that there is a slight increase in squeezing pressure due to the additional effort required to form the tube into the annular cavity [19].…”
Section: Introductionmentioning
confidence: 97%
“…To control this, joining by the squeezegrooving process is introduced which makes use of two independent mandrels. Results indicate that there is a slight increase in squeezing pressure due to the additional effort required to form the tube into the annular cavity [19].…”
Section: Introductionmentioning
confidence: 97%
“…Taking into consideration the above-mentioned limitations of fastening and adhesive bonding for producing hybrid sheet-tube connections, the objective of this paper is to present an alternative joining by forming solution. The idea is to enlarge the applicability domain of deformation-assisted joining by annular sheet squeezing that was recently developed by Alves et al 6,7 to include hybrid sheet-tube connection. The process was originally developed and applied for metallic sheets and tubes and the challenge addressed in this paper is to analyse and control the interactions between cold plastic deformation of polymers and metals in order to produce sound hybrid (polymer-metal) sheettube connections, away from the tube ends.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that numerical simulation is an effective method for studying compressing forming process. 1618 The plastic deformation process and the contact condition at the joining interface can be derived conveniently with finite element simulation. 19,20 Considering the complex contacting character at the joining interface, it is difficult to determine the friction coefficient either by experiment or by simulation.…”
Section: Introductionmentioning
confidence: 99%